PENYULUHAN KESEHATAN TENTANG NAPZA DAN ETIKA PERGAULAN REMAJA DI SMA NEGERI 1 SAPURAN WONOSOBO - Kusyanti, Florentina (Jurnal Pengabdian Dharma Bakti, 2021)
Problems that existed in State Senior High School 1 Sapuran is still there are students who do not know about the ethics of teenage association, so that students sometimes less know to talk with whom so there are some students are less polite both with teachers and with more administration -moremore, the messenger.ini also when sms is also still lack of application about ethics, in addition to this in today's wonosobo region including the growth of drug users is very high ie from January samapai April there are 3 cases about drugs.The Methods of Activity:His method with the students collected in the hall was given lectures and question and answer and then given a questionnaire to find out whether the material provided useful for students.The Aims of this ActivityThis devotion aims to implement tri darma college and to share knowledge in others, especially for students of SMA Negeri 1 Sapuran Wonosobo, so that after given counseling students will be aware about the importance of school ethics and drug enforcement.The Results of this ActivityThis devotion was attended by 159 students and students are very enthusiastic in following this pantuluhan, there are some students who ask, and the result of questionnaires of students, teachers and Schools expects this counseling held every year so that sustainableKeywords: Drugs, Ethics Intercourse TeensÂ